PROSES TRANSFORMASI PT. POS INDONESIA (Studi Kasus Pada Kantor Processing Centre Semarang) - Permanasari, Yarra Waninda; Perdhana, Mirwan Surya (Faculty of Economics and Business Diponegoro University, 2017)
Change is the transformation of the present state into the future state, in the hope of becoming a better state. Office of Processing Centre Semarang is transforming for the company's survival in order to grow continuously with the times, so that it will not decrease business. This research will analyze the transformation process done by Office of Processing Centre Semarang.The purpose of this conceptual research is to present the current literature review related to Change Management. Change is inevitable in every organization. It's just that sometimes the desired changes are hampered by internal or external factors. Various literature related to change management is discussed in this study, along with the upcoming research agenda related to change management.The method used is qualitative method with case study approach. The reason for choosing the method is so that this research can be done in depth and can focus to know the process of transformation done at Office of Processing Center Semarang. The results of this study indicate that the transformation made by the Office of Processing Centre Semarang has not been fully implemented. The unavailability of this transformation is due to employees' ignorance on the part of the staff will be the transformation itself on the Office of Processing Centre Semarang, so that the transformation has not been done according to what the company wants.